The Unicorn, Lammas - Beyerl, Paul, Rev.; Jackson, Prairie (The Rowan Tree Church, 1980)
v.3, no.7 (Lamas [1980]). Beryl, Paul, Rev. & Prairie Jackson, 1952-2010. Rowan Tree Church Periodical Collection. New Age Movements, Occultism and Spiritualism Research Library. Valdosta State University. Dear Humans, A Blessed Harvest! On Lammas Eve, Unicorns of all persuasions will gather, each bringing a basket (woven with care last Beltane) of the finest herbs, grains, and flowers to bring before the Lord and Lady. The herbs will be brewed into chalices of ritual drinks; the fine grains will be ground ‘neath pure white hooves, then worked into a sacred loaf baked in the cauldron; and the flowers braided into a necklace to thank the Earth Mother for her never ending bounty. Uncle folehorn has promised to set off a star shower to entertain the colts and newborn. For those who find cloud filled skies, it is because your stars are shaking loose dew, as much of the Earth is parched and dry.
BE4AFD2B-A501-4190-A8BB-D468FA1AED05 ms150-5_er01_015 Unicorn (Rowan Tree Church) v.3, no.7 (Lamas [1980]). Beryl, Paul, Rev. & Prairie Jackson, 1952-2010. Rowan Tree Church Periodical Collection. New Age Movements, Occultism and Spiritualism Research Library. Valdosta State University. http://hdl.handle.net/10428/2579 v.3, no.7 (Lamas [1980]) Add author: Jackson, Prairie, 1952-2010 Art; Tarot; Poetry.; Reviews.; Herbs--Religious aspects.; Jupiter (Planet)--Religious aspects.; Sexual intercourse--Religious aspects.; Wiccans--Sexual behavior.; Unicorns--Art.; Neopagan gays--Communication.; Short stories; New Age ministers;
Keywords: Unicorn (Rowan Tree Church); Tarot; Poetry; Herbs--Religious aspects; Neopagan gays--Communication; Unicorns--Art; Short stories; Jupiter (Planet)--Religious aspects